The city between freedom and security contested public spaces in the 21st century - Simpson, Deane; Jensen, Vibeke; Rubing, Anders; Andersson, Cecilie (Birkhäuser, part of Walter de Gruyter GmbH, Berlin, 2017)
This publication explores the contested territory between the state and corporate drive to 'securitise' urban space - and the principle of the city as a site for enacting open civil society, participatory democracy, and the freedom of speech and assembly